Communication skills, resources and needs of adults with intellectual disability in residential facilities in the Western Cape and their support staff : a descriptive study - Tonsing, Kerstin Monika (University of Pretoria, 2020)
Mini Dissertation (MA)--University of Pretoria, 2019.